SYNTHESIS OF TRADITION AND UPDATES IN TURKISH (Scientific journal of the Fergana State University, 2025)
This article discusses the interpretation of the image of mother and child in the story "On a Hot Day" by the Turkish writer Yasar Kemal. The tense psychological situation in the story also sheds light on the folklore traditions characteristic of the writer's style. There is also a reaction to the fact that the unhappy childhood of the writer's artistic search was transferred to his works as an image.